Calculation of Greenhouse Gas Emissions (CH4, CO2, and N2O) in Kasihan District in the Agricultural Sector Using the IPCC Application - Lina Hanarisanty; Bayu Ade Pratama (Journal of Engineering Science and Technology Management, 2022)
Climate change has been a challenge for development and humanity is pushing globally. Characterized by climate changes such as temperature, rainfall, humidity, and others. Indonesia is committed to reducing GHG emissions by conduted research in the agricultural land sector, the aim is to determine CH4, N2O, and CO2 emissions and the ratios of CH4, N2O, and CO2 on agricultural land. The type of research used is quantitative and qualitative content analysis. Quantitative data analysis uses statistical data and calculations with the IPCC formula. Meanwhile, qualitative data analysis will describe how agricultural land effects the environment. The research was conducted on agricultural land in Kasihan District. GHG emissions from the agricultural sector come from CH4 emissions in paddy field cultivation with a value of 789,600 CO2e, CO2 in the addition of lime and urea fertilizer with an emission value of 67,150 CO2e, N2O in land agricultural with an emission value of 1,713,098 CO2e, including indirect N2O emissions in the addition of N into the soil due to evaporation and leaching, as well as nonCO2 originating from burning biomass in agricultural activities